Noun juxtaposition for predication, possession, and conjunction: Beyond ambiguity avoidance - Shogo Mizuno (Linguistic Typology at the Crossroads)
This paper asks whether ambiguity avoidance influences the use of certain linguistic forms, using noun juxtaposition as a case study. Noun juxtaposition is one of the strategies for expressing predication, possession, and conjunction, and is widely used across the world’s languages. Despite its extensive use, few studies have investigated noun juxtaposition cross-linguistically. One notable exception is Frajzyngier et al. (2002), who argue that the use of noun juxtaposition is constrained within a single language due to ambiguity avoidance. However, counterexamples to this hypothesis exist. This study points out that their sample is skewed towards African languages, and thus, their findings likely reflect African areal patterns. From this perspective, a comprehensive cross-linguistic examination of noun juxtaposition is still lacking. Therefore, based on a balanced 72-language sample, this paper explores which functions tend to be expressed by noun juxtaposition, whether there are any areal patterns concerning its use, and whether its use is constrained by ambiguity. Since noun juxtaposition is, by definition, the most efficient strategy for these three functions in terms of formal complexity, the research conducted in this study contributes to discussions on whether ambiguity or efficiency is more important for the use of certain linguistic forms. Based on the empirical findings, this study suggests that efficiency plays a more important role than ambiguity.